Effect of melt conditioning on heat treatment and mechanical properties of AZ31 alloy strips produced by twin roll casting - Das, Sanjeev; Barekar, NS; Fakir, Omer El; Wang, Liliang; A. K., Prasada Rao; Patel, JB; Kotadia, HR; Bhagurkar, A; Dear, John P; Fan, Z (Elsevier Ltd, 2014)
In the present investigation, magnesium strips were produced by twin roll casting (TRC) and melt conditioned twin roll casting (MC-TRC) processes. Detailed optical microscopy studies were carried out on as-cast and homogenized TRC and MC-TRC strips. The results showed uniform, fine and equiaxed grain structure was observed for MC-TRC samples in as-cast condition. Whereas, coarse columnar grains with centreline segregation were observed in the case of as-cast TRC samples. The solidi fication mechanisms for TRC and MC-TRC have been found completely divergent. The homogenized TRC and MC-TRC samples were subjected to tensile test at elevated temperature (250–4001C). At 2501C, MC-TRC sample showed significant improvement in strength and ductility. However, at higher temperatures the tensile properties were almost comparable, despite of TRC samples having larger grains compared to MC-TRC samples. The mechanism of deformation has been explained by detailed fractures surface and sub-surface analysis carried out by scanning electron and optical microscopy. Homogenized MC-TRC samples were formed (hot stamping) into engineering component without any trace of crack on its surface. Whereas, TRC samples cracked in several places during hot stamping process